Gambaran Bakteri Kontaminan pada Sikat Gigi - Perdina Nursidika; Patricia Gita Naully; Linda Ayu Lestari (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2018)
Abstract: DESCRIPTION OF BACTERIAL CONTAMINTANT IN TOOTHBRUSH. Brushing activity is an effort to keep oral hygiene from pathogenic microorganisms that can cause infection. Oral infection has been an increasingly common risk factor for systemic disease. Oral infections, especially periodontitis, can affect travel and pathogenesis of a number of systemic diseases, such as cardiovascular disease, bacterial pneumonia, diabetes mellitus, and low birth weight. Keeping your teeth and mouth clean is not enough just brushing your teeth, but replace the toothbrush for a maximum of three months. This study aims to identify the contaminant bacteria found on toothbrushes that have been used for more than 3 months. The method of identification by planting the isolation result of 20 toothbrushes has been used for more than three months on selective media ie blood agar (AD), McConkey Agar (MCA), Eosin Methylen Blue (EMB), Manitol Salt Agar (MSA) . The results showed that all samples of toothbrush were contaminated with Streptococcus and Staphylococcus, 16 samples were Klebsiella (80%), four samples (20%) were Proteus, and one sample (5%) was contaminated with Escherichia. All of the toothbrush samples showed to have been contaminated by bacteria. Bacterial contamination of the toothbrush can be caused by the storage of a toothbrush that is too close to the toilet and toilet, possibly exposed through aerosols containing intestinal bacteria. This toothbrush contamination plays an important role in both oral and systemic diseases, including septicemia and gastrointestinal, respiratory cardiovascularmy, and kidney problems. Abstrak: GAMBARAN BAKTERI KONTAMINAN PADA SIKAT GIGI. Kegiatan menyikat gigi merupakan upaya untuk menjaga kebersihan gigi dan mulut dari mikroorganisme pathogen yang dapat menyebabkan infeksi. Infeksi mulut telah menjadi faktor risiko yang semakin umum untuk penyakit sistemik. Infeksi mulut, terutama periodontitis, dapat mempengaruhi patogenesis dari sejumlah penyakit sistemik, seperti penyakit kardiovaskular, pneumonia bakteri, diabetes mellitus, dan berat badan lahir rendah. Menjaga kebersihan gigi dan mulut tidak cukup hanya menyikat gigi saja, melainkan mengganti sikat gigi maksimal tiga bulan sekali. Penelitian ini bertujuan untuk mengidentifikasi bakteri kontaminan yang terdapat pada pada sikat gigi yang telah digunakan selama lebih dari 3 bulan. Metode identifikasi dengan melakukan penanaman hasil isolasi 20 sikat gigi yang telah digunakan selama lebih dari tiga bulan pada media selektif yaitu agar darah (AD), McConkey Agar (MCA), Eosin Methylen Blue (EMB), Manitol Salt Agar (MSA) dengan metode gores.  Hasil penelitian menunjukkan semua sampel sikat gigi terkontaminasi Streptococcus dan Staphylococcus, 16 sampel terdapat Klebsiella (80%), pada empat sampel (20%) terdapat Proteus, dan satu sampel (5%) terkontaminasi Escherichia. Semua sampel sikat gigi menunjukkan telah terkontaminasi oleh bakteri. Kontaminasi bakteri pada sikat gigi ini dapat disebabkan oleh penyimpanan sikat gigi yang terlalu dekat dengan jamban, sehingga kemungkinan terpapar melalui aerosol yang mengandung bakteri usus. Kontaminasi sikat gigi ini memegang peranan penting pada penyakit oral maupun sistemik, termasuk septikemia dan gastrointestinal, kardiovaskularm pernapasan, dan masalah ginjal.